Meningkatkan Hasil Belajar Mata Pelajaran IPA Materi Ciri-Ciri Khusus Makhluk Hidup Hewan Menggunakan Metode Pembelajaran Jigsaw Pada Siswa Kelas VI.A SD Negeri 217/X Parit Culum I Tahun Pelajaran 2022/2023 - Nurmayani Nurmayani (Journal on Education, 2023)
Science learning at the SD/MI level still tends to use the lecture method, assignments and exercises from the teacher. The subject matter is conveyed directly to students and students only listen and record explanations from the teacher, then science practicum is also rarely carried out. The teacher only informs facts and concepts through the lecture method and minimizes student involvement. Students are given questions that are more likely to be rote. Questions related to higher thinking abilities such as conducting experiments and then concluding the results of experiments are rarely done by teachers. The purpose of this study was to find out the increase in learning outcomes in science subject material on the special characteristics of living animals using the jigsaw learning method for students in class VI.a SD Negeri 217/X Parit Culum I in the 2022/2023 academic year. This type of research is Classroom Action Research (CAR). The research subjects were students of class VI.a SD Negeri 217/X Parit Culum I, Muara Sabak Barat District, totaling 10 male students and 11 female students. Based on the results of the research implementation, the researchers concluded that the jigsaw method could improve learning outcomes in class VI students .a Material on the special characteristics of living animals in SD Negeri 217/X Parit Culum I for the 2022/2023 academic year. The class average increased from 65 in cycle I to 90 in cycle II, and this PTK was considered successful. To all teachers at SD Negeri 217/X Parit Culuum I, Muara Sabak Barat District, in an effort to improve students' understanding of learning, they can use the jigsaw method with the CTL (Contextual Teaching Learning) approach in the teaching and learning process.